Atomistic simulations reveal the photoactivation mechanism of a carotenoid-binding photoreceptor - Amanda Arcidiacono; Mattia Bondanza; Lorenzo Cupellini; Benedetta Mennucci (Proceedings of the National Academy of Sciences, 2026)
The orange carotenoid protein (OCP) is a key photoreceptor in the photoprotection of cyanobacterial antenna complexes. Its peculiar activity is governed by a bound keto-carotenoid that functions both as a light sensor and an energy quencher. Upon blue light absorption, OCP transitions from an orange resting state (OCP O ) to a red active state (OCP R ) through carotenoid translocation into the N-terminal domain, followed by domain separation. Despite extensive studies, the molecular mechanism underlying photoactivation has remained unresolved. Here, we integrate excited-state nonadiabatic dynamics with enhanced sampling molecular dynamics, to reveal the entire photoactivation pathway at atomistic resolution. Our simulations identify a trans -to- cis photoisomerization of the bound keto-carotenoid as the critical photochemical event that initiates translocation. This cis isomer not only matches transient spectroscopic signatures observed experimentally but also exhibits the specific interactions with the protein required to enable translocation and domain separation. Finally, we uncover a multiphoton mechanism responsible for regenerating the all- trans configuration observed in the OCP R –antenna complex. These findings provide a mechanistic framework for OCP photoactivation, linking photochemistry with large-scale conformational changes. Our work highlights the central role of carotenoid photoisomerization and demonstrates the power of advanced atomistic simulations in dissecting the functional dynamics of photoreceptor proteins.